Expanding Kazakhstan’s agricultural exports: Opportunities and Challenge (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
This paper considers of opportunities expanding Kazakhstan’s agricultural export. This is due to thefact that Kazakhstan is now widely regarded as a key player on world agricultural markets, with considerableexport potential in the wheat, beef and dairy sectors. This analysis offers new insights into the constraintsthat hamper further economic growth and provides an assessment of the government’s agriculturaldevelopment strategy. Along with, in this paper discusses the challenges of expanding Kazakhstan’sagricultural exports. Meanwhile, to being essential for food security and social stability, agriculture is alsoan essential part of the government’s strategy to diversify the economy and reduce its dependence onmineral and fossil fuel resources. Agriculture has consistently been identified as a priority sector in governmentprograms for diversification, export promotion and the attraction of foreign direct investment.